Culture, politics and being more equal than others in COVID-19: some psychological anthropology perspectives. (June 2021) - Pillay, Indira
The COVID-19 pandemic changed how we view the world, human behaviour, and societal structures and institutions. The emerging subdiscipline of psychological anthropology is well placed to provide a perspective on the way individuals and communities are affected by and respond to the pandemic, as well as the fallout from government responses and prevention strategies. Moreover, this viewpoint enables insights into the workings of societal structures and agents of power in the context of a health crisis that is worsened by poverty, inequality, and structural violence. How communities respond and adapt to the 'new normal' are critical to holding governing structures accountable in situations where poor leadership, mismanagement, and unethical behaviour have been evident.